1996
DOI: 10.1021/cm950582x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fluorescent, Low-Symmetry Triphenylene Discotic Liquid Crystals:  Tailoring of Mesomorphic and Optical Properties

Abstract: A series of monofunctionalized triphenylene-based discotic liquid crystals were synthesized starting from 2-hydroxy-3,6,7,10,11-pentakis(pentyloxy)triphenylene. These compounds are unique in that they possess a single electron-withdrawing group (and consequently a large dipole moment) connected directly to the polyaromatic core. All of the new liquid crystals show a significantly broader range of mesogenicity relative to the parent compound 2,3,6,7,10,11-hexakis(pentyloxy)triphenylene. Moreover, some of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 28 publications
(29 reference statements)
2
45
0
2
Order By: Relevance
“…[115] Die induzierte Abnahme der Molekülabstände um 6 % für Drücke bis 17 kbar ist jedoch zu klein, um die elektronische Struktur und damit die optoelektronischen Eigenschaften zu modifizieren. Dagegen fanden die Arbeitsgruppen um Ringsdorf, [116] Kumar [117] und Bushby [118] unabhängig voneinander, dass stark elektronenziehende Bromoder Cyansubstituenten (in 48 e bzw. 48 f) nicht nur die Mesophasen stabilisieren, sondern auch die Fluoreszenzquantenausbeuten erhöhen, die für die Entwicklung optoelektronischer Bauteile wichtig sind.…”
Section: Schema 15unclassified
“…[115] Die induzierte Abnahme der Molekülabstände um 6 % für Drücke bis 17 kbar ist jedoch zu klein, um die elektronische Struktur und damit die optoelektronischen Eigenschaften zu modifizieren. Dagegen fanden die Arbeitsgruppen um Ringsdorf, [116] Kumar [117] und Bushby [118] unabhängig voneinander, dass stark elektronenziehende Bromoder Cyansubstituenten (in 48 e bzw. 48 f) nicht nur die Mesophasen stabilisieren, sondern auch die Fluoreszenzquantenausbeuten erhöhen, die für die Entwicklung optoelektronischer Bauteile wichtig sind.…”
Section: Schema 15unclassified
“…On the contrary, when in the I-2d compound the exchange is done at meta position -meta-pentoxy chain is replaced with the meta-hexyl substituentthe resulting I-2a compound shows the lower clearing point, about 33°C. The meta-alkyl group is more likely to be situated nearly perpendicular to the phenyl ring [37] and it seems this is the case. When orthooctyloxy substituent (R4) in the compound I-2g is converted into ortho-nonyl chain, the clearing temperature in I-2f compound falls drastically about 130°C.…”
Section: Mesomorphismmentioning
confidence: 97%
“…Reproduced with permission from [31] mobility on transition from mesophase to crystal phase is a common feature of a number of discotics and is ascribed to the greater short-range structural order within the crystal packing of the molecules. It is found that molecular order within the columnar phase of discotic triphenylenes can also be changed by the variation of the lateral chain or by direct polar substitutions (compound 4) on the aromatic core [41,42]. van de Crats et al reported TOF and PR-TRMC hole mobilities of about 0.01 cm 2 V −1 s −1 in the columnar phase of triphenylene dimer 5 [43].…”
Section: P-type Discotic Moleculesmentioning
confidence: 99%